Penanggulangan Bentrok Massa Akibat Konflik Pertanahan Oleh Satuan Brimob Polda Sumatera Utara - Arke Furman Ambat; Alpi Sahari; Surya Perdana (Mahesa Research Center, 2020)
The handling of mass clashes due to land conflicts carried out by the North Sumatra Regional Police Mobile Brigade Unit will not be effective without the support of the community. One effective step to anticipate mass riots arising from land problems as high-level Kamtibmas disturbance is to implement the polemical synergy of the Kamandahan Patrol conducted by the North Sumatra Police Mobile Brigade first applying the mapping of land conflict-prone areas as conflicts arising from natural resource conflicts that have the potential to cause mass riots. This research uses normative legal research, descriptive analysis. The handling of mass clashes due to land conflicts carried out by the North Sumatra Regional Police Mobile Brigade Unit will not be effective without the support of the community. The obstacle of the North Sumatra Regional Police Mobile Brigade in overcoming mass clashes due to land conflicts is the limited number of personnel in quantity and quality that has not been running optimally so that it has an impact on community assessments in handling mass riots due to horizontal conflicts arising from land issues including Knowledge, Skill, Attitude . Efforts made by the North Sumatra Regional Police Mobile Brigade were to apply the Kamandahan Patrol managerial method in anticipating mass clashes caused by land conflicts which included planning, organizing, implementing, monitoring and controlling were considered to be less than optimal.